Airborne Water Vapor Differential Absorption Lidar (DIAL) measurements in the Tropics - Kiemle, Christoph (2016)
Presented were results from the NARVAL-S campaign across the subtropical Atlantic and near Barbados, using the DLR WALES lidar onboard the new German HALO research aircraft. In the subtropical lower troposphere we have encountered scattered clouds with tops at two distinct levels, embedded in a layer of high humidity. Measuring the variability of water vapour around these clouds will shed light on cloud-humidity interactions. Similarly, cloud-aerosol relationships can be investigated with this unique instrumentation. Vertical fluxes of latent heat can be assessed using auxiliary data. Finally we have done feasibility studies for ESA for a future implementation of such an instrument on a satellite